(untitled) (Portuguese Journal of Family Medicine and General Practice, 2008)
The Added Therapeutic Value (ATV) means a better efficacy, safety and / or convenience of a drug in comparison with the best therapeutic alternative till now.ATV can also signify the drug effect with an acceptable benefit / risk ratio to a therapeutic necessity in a clinical indication without drugs.The demonstration of the ATV,which is a real therapeutic innovation and not only a commercial or technological innovation, must be performed through the Evidence-Based Medicine methodologies.